Treadmill Exercise Reverses Depression Model-Induced Alteration of Dendritic Spines in the Brain Areas of Mood Circuit - Zhuang, Pu-Chao; Tan, Zhi-Nei; Jia, Zi-Yan; Wang, Biju; Grady, James J.; Ma, Xin-Ming (Frontiers in Behavioral Neuroscience, 2019)
Depression is one of the most prevalent psychiatric disorders. Exercise has been shown to be effective in the amelioration of depression, but the underlying mechanism remains largely unknown. Alterations in the density and morphology of dendritic spines are associated with psychiatric diseases. Chronic unpredictable mild stress (CUMS) is an established animal model of depression. The aim of this study was to determine whether treadmill exercise reverses CUMS-induced both depression-like behaviors and alterations in spine density and morphology of the principal neurons in the brain areas of the mood circuits including the hippocampus, medial prefrontal cortex (mPFC), nucleus accumbens (NAc) and basolateral amygdala (BLA). Male rats were randomly divided into four groups: control, CUMS, exercise, and CUMS+exercise. CUMS-induced depression-like behaviors were evaluated by the sucrose preference test. Golgi staining was used to visualize dendritic spines. Our results showed that CUMS-induced depression-like behaviors characterized by a decrease in sucrose consumption were accompanied by a decrease in spine density and a change in spine morphology in the pyramidal neurons of both the hippocampal CA3 area and the mPFC, and an increase in spine density and an alteration in spine shape in both the NAc medium spiny neurons and the BLA neurons; exercise reversed both CUMS-induced depression-like behaviors and alterations in dendritic spines. This study provides important information for understanding the mechanism through which exercise ameliorates CUMS-induced depression-like behaviors.